Analisis Perkembangan Kognitif Pada Anak Autis Di Flexi School Banda Aceh - Putri Regina Lestari; Syahnaz Saqila; Reisatul Ulya; Hijriati Hijriati (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
There are many challenges and problems faced by autistic children regarding cognitive development. Occupational therapy is a treatment that aims to help someone who has physical, mental and cognitive limitations. This therapy is carried out so that sufferers can become less dependent on other people to live their daily lives. So they can maximize their cognitive potential. The aim of this research is to obtain information about cognitive development in autistic children in flexi schools and how to handle it. The method used in this research is descriptive qualitative research. The subject of this research is a student at a flexi school and the object of this research is occupational therapy to improve cognitive development in autistic children. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The data collection techniques used were field observation, interviews and documentation. The conclusion from the results of this research is that children experience an increase in cognitive development, namely they are able to understand the meaning of simple commands, the order and grouping of objects, and the sequence of actions. However, they still need repetition to strengthen their understanding